2008
DOI: 10.1242/jcs.023234
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic nuclear reorganisation driven by aHoxb1transgene transposed intoHoxd

Abstract: Summary The extent to which the nuclear organisation of a gene impacts on its ability to be expressed, or whether nuclear organisation merely reflects gene expression states, remains an important but unresolved issue. A model system that has been instrumental in investigating this question is the murine Hox clusters. Nuclear reorganisation and chromatin decondensation, initiated towards the 3' end of the clusters, accompanies activation of Hox genes in both differentiation and development, and may be linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Vice versa, not observing an effect does not exclude that an early act of transcription prior to (drug) treatment was responsible for setting up the 3D structure measured. Nuclear repositioning independent of changes in transcription has been observed before, but only for some individual loci and measured relative to nuclear landmarks like the chromosome territory or nuclear lamina (Morey et al 2008;Peric-Hupkes et al 2010). Our data provide highresolution molecular interaction maps that uncouple topological changes from transcription on a chromosome-wide scale.…”
Section: Transcription and The Shape Of The Inactive X Chromosomesupporting
confidence: 50%
“…Vice versa, not observing an effect does not exclude that an early act of transcription prior to (drug) treatment was responsible for setting up the 3D structure measured. Nuclear repositioning independent of changes in transcription has been observed before, but only for some individual loci and measured relative to nuclear landmarks like the chromosome territory or nuclear lamina (Morey et al 2008;Peric-Hupkes et al 2010). Our data provide highresolution molecular interaction maps that uncouple topological changes from transcription on a chromosome-wide scale.…”
Section: Transcription and The Shape Of The Inactive X Chromosomesupporting
confidence: 50%
“…In order to be activated, a gene has to be relocated outside the chromosome territory and its chromatin structure decondensed to a level consistent with the existence of the 30-nm chromatin fiber (35). Poised (potentially active in transcription) and active chromatin domains likely exist in the form of the 30-nm fibers (13 and 37; but also see reference 51).…”
Section: Enhancer Action In Chromatinmentioning
confidence: 99%
“…The simplest, most straightforward model suggests that chromatin-compacted DNA supports efficient EPC. Functionally active genomic regions usually contain E-P spacer DNA that is compacted up to ϳ30-fold into the 30-nm chromatin fiber (35). Therefore, the range of action of the recruiting mechanism could be increased up to 30-fold (to ϳ20-to 30-kb range), provided that the chromatin structure is dynamic.…”
Section: Enhancer Action In Chromatinmentioning
confidence: 99%
“…This phenomenon, temporal-spatial colinearity, is pivotal for the correct patterning of animal bodies and depends on the proper silencing of 5= HOX genes (1). In a cellular model, a progressive transition from a repressed to an active chromatin state along the cluster from 3= to 5= has been proposed to mediate HOX colinearity (2)(3)(4)(5), accompanied by nuclear reorganization (6)(7)(8)(9) and changes in the higher-order chromatin structure of the clusters (10). A recent study revealed a transition in HOX cluster architecture from an initial single 3-dimensional (3-D) structure to a bimodal state that separates the active and inactive genes during colinear activation of HOX genes in mouse embryos (11).…”
mentioning
confidence: 99%